The rhizosphere revisited: root microbiomics - Bakker, Peter A.; Berendsen, Roeland L.; Doornbos, Rogier F.; Wintermans, Paul C.; Pieterse, Corné M. (Frontiers in Plant Science, 2013)
The rhizosphere was defined over 100 years ago as the zone around the root where microorganisms and processes important for plant growth and health are located. Recent studies show that the diversity of microorganisms associated with the root system is enormous. This rhizosphere microbiome extends the functional repertoire of the plant beyond imagination. The rhizosphere microbiome of Arabidopsis thaliana is currently being studied for the obvious reason that it allows the use of the extensive toolbox that comes with this model plant. Deciphering plant traits that drive selection and activities of the microbiome is now a major challenge in which Arabidopsis will undoubtedly be a major research object. Here we review recent microbiome studies and discuss future research directions and applicability of the generated knowledge